Excess pore water pressure caused by the installation of jet grouting columns in clay. (September 2020) - Wang, Zhi-Feng; Shen, Shui-Long; Modoni, Giuseppe; Zhou, Annan
Abstract: The injection of large volumes of pressurized water and grout into the subsoil during jet grouting generates a sudden increase in excess pore water pressure. This study proposes a theoretical approach to evaluate the variation in excess pore water pressure caused by the installation of a jet grouting column in clay, accounting for the chronological sequence of construction. The jet grouting column installation is simulated through the undrained expansion of a series of spherical cavities. Partial dissipation during the construction process is considered due to the gradual installation of the grouting columns. The relationship between the ultimate cavity radius ( a u ) and the radius of the jet grouting column ( r c ) is established to represent the influences of both jetting parameters and soil properties on the generated excess pore water pressure. The proposed model is validated using two case studies, one conducted in Singapore marine clay and the other in Shanghai soft clay.